RESPONSE OF SEASHORE PASPALUM TURFGRASS TO IRRIGATION PERIODS AND HUMIC ACID - Boshra El-Sayed; Sayed Shahin; Tarek Noor El-Deen; Mahmoud El-Ashwah (Scientific Journal of Flowers and Ornamental Plants, 2016)
A trial was carried out in the open field at the Nursery of Hort. Res. Inst., Giza, Egypt during 2014 and 2015 seasons to examine the effect of irrigation periods, alone or plus foliar spraying with humic acid on growth and quality of seashore paspalum (Paspalum vaginatum Swartz). The irrigation periods were once every 3, 6 or 9 days, and the humic acid (liquid organic fertilizer, NPK 10:10:10) was applied at 20 ml/l, after each grass cut. The turfgrass was cultivated by sprigs in plastic trays (40×30×12 cm) filled with a mixture of sand and clay (1:1, v:v). The obtained results indicated that plant height, covering rate percentage, number of shoots/tray and grass fresh and dry weights were descendingly decreased in the two seasons with elongating the irrigation period to reach the minimum values when irrigation was done once every 9 days. However, applying humic acid significantly improved all previous traits, even for the 9 days interval treatment. The opposite was the right regarding the content of chlorophyll a, b and carotenoids (mg/g fresh weight), total sugars (mg/g dry weight), as well as indoles and phenols (mg/100 g fresh weight), as they were progressively increased with prolonging irrigation period. Humic acid treatment was also led to raised content of the different constituents mentioned above. The supremacy in vegetative growth parameters was achieved by the combination of irrigation every 3 days + 20 ml/l humic acid, but in chemical composition it was by irrigation every 9 days + 20 ml/l humic acid combined treatment. So, it could be recommended to spray humic acid at the rate of 20 ml/l on the foliage of seashore paspalum turf after each cut at irrigation rate of once every 9 days to obtain the best growth and performance from a commercial point of view.